MENJADI BIJAK BAGI PEMILIH PEMULA BERDASARKAN INFORMASI DARI MEDIA SOSIAL DI KABUPATEN KEPULAUAN MERANTI - Amir Syamsuadi; Diki Arisandi; Seri Hartati; Bahjatul Murtasidin (LPPM Universitas Abdurrab, 2019)
Social media has more capabilities of transferring ideas, disseminating various purposes, including political campaign content through social media more quickly and almost without any boundaries. Social media can also as the communication tools where everyone influences each other, including in terms of influencing voters and in this case it will become a novice voter for high school students in the Meranti Islands Regency. Novice voters are identical to smartphones and social media. This activity aims to educate novice voters in determining and making choices based on what they experienced in social media so that they have sufficient knowledge and become wiser, and also ready to participate in the general election.